Feasibility of a theory-based intervention towards benzodiazepine deprescribing in Belgian nursing homes: protocol of the END-IT NH cluster-randomised controlled trial - Séverine Henrard; Anne Spinewine; Sandy Tubeuf; Catherine Pétein; Perrine Evrard; Tina Chevallereau; Josephine Aikpitanyi (BMJ Open)
Introduction Despite several calls to deprescribe benzodiazepine receptor agonists (BZRA) in older adults, their use among nursing home residents (NHRs) remains high. Therefore, we developed an intervention targeting general practitioners’ and healthcare professionals’ behaviours regarding BZRA deprescribing in nursing homes (NHs): The END-IT NH (bENzodiazepines Deprescribing InTerventions Nursing homes) 6-component intervention. Before moving on to a large-scale effectiveness and cost-effectiveness evaluation, this feasibility study aims at: (1) assessing the feasibility of the intervention implementation in NHs, (2) assessing the feasibility of conducting a larger-scale evaluation, in terms of recruitment and data collection and (3) conducting an exploratory cost-effectiveness evaluation.Methods and analysis We will conduct a cluster-randomised controlled trial in a sample of 6 NHs, with 10–15 NHRs included per NHs. Four NHs will be randomised into the intervention group, and two NHs will deliver usual care (control group). Data collection will occur at baseline, 3, and 6 months (study end). We will collect information to explore implementation fidelity, mechanisms of impact and contextual factors at patient-level, NH-level and healthcare professional-level, using both quantitative and qualitative measures. The feasibility of the study conduction will be assessed by measuring recruitment and attrition rates and completeness of data collection. An exploratory cost-effectiveness evaluation will be conducted based on quality of life and healthcare use and cost data.Ethics and dissemination This study protocol received approval from the ethical committee of CHU UCL Namur on the 20 June 2023. All data are confidential and will be anonymised prior to analysis. De-identified data will be shared on a data depository with a 2-year embargo. The results of the study will be disseminated through a scientific paper and will be communicated to local stakeholders and policymakers through a local symposium.Trial registration number NCT05929443.